Katechizm rzymski Soboru Trydenckiego a współczesne dokumenty Kościoła katolickiego na temat Żydów i judaizmu - Ignatowski, Grzegorz (Śląskie Studia Historyczno-Teologiczne, 2005)
After the last Vatican Council some authors and documents on the Catholic-Jewish relations emphasize that The Roman Catechism of the Council of Trent issued in 1556 teaches that not all the Jews, Jesus’ contemporaries, are responsible for the Crucifixion. In the first part of the presented article the author explains why the Secretariat for Promoting Christian Unity, which had prepared the Declaration on the Relationship of the Church to Non-Christian Religions Nostra Aetate (accepted by the Council in October 28, 1965, clause nr 4 of which deals with the Jews), did not quote The Roman Catechism, which teaches that no single person but all men are guilty of Jesus’ death: „This guilt seems heavier on our part than on the Jews’, since according to the testimony of the apostle »had they known it, they would never have crucified the Lord of glory« (1 Cor. 2, 8); while we, on the contrary, professing to know him, yet denying him by our actions, seem in some sort to lay violent hands in him”. The passage was cited by some Fathers of the Second Council and by the some post-Conciliar documents. The author of the article is convinced that in the matter of the death of Jesus Christ it is necessary to distinguish between the theologi-cal guilt and the historical responsibility. From the point of view Christian theology all human beings are guilty of Jesus’ death. The Christ voluntarily underwent the Passion because of the sins of all men. The last Council wanted to emphasize that the Jewish people, as a whole, was not responsible for the Crucifixion, from the historical point of view. The main motive of the decision of the Council was the fact that Jesus’ cruel death and especially the accusation of the Jewish people of the Crucifixion have been the cause of the lamentable deterioration of the relations between the Church and Judaism. As the passage quoted from The Roman Catechism dealt with the theological aspect of the guilt of the Crucifixion, it could not be a useful document for the last Council. Moreover, the sixteenth century catechism, from the historical perspective, stresses clearly that the pagans and the Jews were responsible for the Passion. The last part of the article discusses the post-Conciliar documents, which quote The Roman Catechism. The discussion shows that those documents, recalling the 16th century catechism, emphasize the theological mining of Christ’s death.